Influencia de la iluminancia y tiempo de remoción de materia orgánica, expresada en DBO5, de efluentes de remojo en curtiembres, utilizando Chorella pyrenoidosa en un fotobioreactor a escala laboratorio - Carbonell Muñoz, Jhossef Edinson (2018)
In this study, the influence of illuminance and time of removal of organic matter, expressed in BOD5, was determined in soaking effluents from the Ecológica del Norte EIRL tannery, using the Chorella pyrenoidosa species, in a Bubble Column photobioreactor (BCR) to laboratory scale. A prototype incubator for the microalgae was manufactured, where the necessary conditions for the cultivation of the strain were controlled. For the treatment, two phases were considered; in the first phase, the microalgae and effluent strain was used in a 1: 1 ratio; to natural light conditions and illuminance intensities of 2800 Lx, 5100 Lx and 8200 Lx which was controlled in the incubator. In the second phase, the removal of organic matter expressed in BOD5 was evaluated at the intensity of light of greater efficiency in the removal obtained in the first phase, at different proportions of effluent - microalgae. Both phases were carried out at constant aeration conditions of 4 L / min and 24-hour photoperiod for 10 days. Concluding that the illuminance has a direct influence on the growth of the species Chorella pyrenoidosa, which is visualized in the results obtained in the first phase, where it was demonstrated that the best illuminance for the removal of organic matter was 5100 Lx, to these conditions we obtained an 89% removal of organic matter expressed in BOD5. The time also influences the removal of organic matter from the soaking stage, this influence is reflected in the percentage of organic matter removal in the first two days, 57%. With the result of the higher efficiency illuminance, the percentage of removal in the different proportions of effluent - microalga was evaluated. The results show that the microalga achieved the removal of organic matter expressed in BOD5 of 95%